Determinant factors for the level and valorification of wheat production in the European Union - Ruxandra-Eugenia Pop (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The wheat crop is very important worldwide and the wheat demand is expected to increase in the future, as a result of the population number growth and dietary changes. So, the wheat production grow represents a significantchallenge that the agriculture must face with, in order to ensure the food security at the global level. In the European Union there are important concerns to identify and assess the current factors that influence and determine the wheat production level and it's efficient valorification. In this paper are presented such significant factors, of different types, as follows: environmental, technological, management, market, taken into consideration producers and farmers current points of view. The personal contribution of the author includes graphical representations, which are useful for technological factors modeling and assessment, realized using adequate software tools.
Keywords: 330; wheat production; technological factors reprezentation